What Is the Role of AI in Anxiety Disorder Treatment? - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2015)
Anxiety disorders are the most prevalent psychiatric conditions globally, characterized by excessive and persistent worry that can significantly impair daily...
Keywords: AI in Mental Health; Anxiety; Disorder; Treatment; Artificial Intelligence; Machine Learning; Healthcare